Outcomes of Corneal Tattooing by Rotring Painting Ink in Disfiguring Corneal Opacities - Alahmady H. Alsmman; Engy Mohamed Mostafa; Amr Mounir; Mahmoud Mohamed Farouk; Mohamed Gamal Elghobaier; Gamal Radwan (Journal of Ophthalmology)
Aim. To evaluate corneal tattooing with Rotring painting ink (Rotring Ink, Hamburg, Germany) as an available and affordable surgical technique to improve cosmetic appearance in the eyes with disfiguring corneal opacities. Methods. Fifty-three blind eyes with corneal disfiguring opacities underwent corneal tattooing using Rotring painting ink (Rotring Ink, Hamburg, Germany) by multiple transepithelial intrastromal injections under topical anesthesia. Complete ophthalmic examination and ocular ultrasonography were performed, and photographs of the patients’ eyes were taken. Follow-up period was at least 12 months. Results. On the first postoperative day, all patients presented with mild conjunctival injection and foreign body sensation. After the end of the follow-up period, 51 patients (96%) were satisfied of cosmetic appearance while only 2 patients (4%) post-op cosmetic results were less than their expectations; however, they were better in appearance. No major complications like corneal erosions; corneal ulcers or corneal melting was noted in any case. Conclusions. Corneal tattooing with Rotring painting ink in blind disfigured eyes achieves favourable cosmetic results and is associated with high patient satisfaction. With better case selection, a high post-op satisfaction was achieved. Corneal tattooing acts as an alternative to more sophisticated and expensive cosmetic reconstructive surgery. This trial is registered with ISRCTN46626979.